Ontogenetic and sexual variation in the sagitta otolith of Menticirrhus americanus (Teleostei; Sciaenidae) (Linnaeus, 1758) in a subtropical environment - Maichak de Carvalho, Barbara (2020)
This study aimed to verify variations in the form of the sagitta otolith of Menticirrhus americanus as to their ontogeny, sex and stage of such structure. Ontogenetically were found significant differences (p < 0.05) for all shape indices (aspect ratios, shape factor, rectangularity, ellipticity, relative surface of sulcus acusticus) and also in the wavelet of the otolith. The CVA presented a 98.6% correct reclassification of the otolith between interval class. Sexual variations were found in the wavelet and in the relative surface of sulcus acusticus index. Between adult females and young females, differences were not detected in the wavelet and rectangularity, but significant differences were found in all other shape indices. The CVA presented a 79.6% correct reclassification of the otolith of the sexes and stages of life sampled. Young females and adults females showed highest correct percentage of classification. The results of this study demonstrate for the first time the influence of the ontogenetic variation and sexual in the form of the otoliths.